EFFECTS OF SOME BORON COMPOUNDS AND/OR WATER REPELLENTS ON THE HIGROSCOPICITY OF BRUTIA PINE (Pinus brutia Ten.) WOOD - M. Kemal YALINKILIÇ; Ergün BAYSAL; Zafer DEMİRCİ (Pamukkale University Journal of Engineering Sciences, 1995)
As a water borne salt type, boron salts also tend to increase in hygroscopicity of wood. This phonomenon is known as one of the disadvantages of these salts in wood preservation in spite of their protective effectiveness against biological agents and fire. This study was designed to determine the rate of higroscopicity both treated and untreated Brutia pine wood. Impregnation solutions of boric acid (BA) and sodium perborate (SP) was prepared by water and polyethylene glycol (PEG)-400 (P4). Additionally, some water repellents (WRs) such as paraffin wax (P), styrene (St), methylmethacrylate (MMA) and isocyanate (ISO) were used to keep the hygroscopicity level of wood at an acceptable level. Results indicated that paraffin wax and WRs were considerably lowered the hygroscopicity of wood. 4 homogenity groups were formed from the statistical analysis as follows (from the most hygroscopic treatments to lesser, respectively): (1) P4, (2) P4+BA or SP, control, (3) WRs, BA or SP+WRs and, (4) P+BA+Bx (% 15 aqueous solution). None of the solutions increased the hygroscopicity of wood than control treatments, but P4 (P? 0.05).